Pentingnya Pelatihan E-commerce Guna Meningkatkan Penjualan UMKM - lesi* lesi (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
E-commerce or electronic commerce is currently growing rapidly in an era of increasingly advanced technology along with the times.E-commerce is one of the trade or sales media that is in great demand by the public today in order to be able to sell, buy, and promote products using online media as online buying and selling transactions. Selling clothing products using e-commerce is very profitable for both sellers and buyers. With increasingly sophisticated technology and gadgets, buyers no longer bother to choose the clothes they want without being tired of going around choosing clothes, even though only by using cellphones, buyers can already buy clothes that are outside the city and even abroad using e-commerce, so sellers can market their products, the product is not only in the surrounding area.